Comparison of Laparoscopic and Conventional Repair in the Treatment of Peptic Ulcer Perforation - Anıl Ergin; Yasin Güneş; İksan Taşdelen; Mehmet Mahir Fersahoğlu; Nuriye Esen Bulut; Ahmet Çakmak; Emre Teke; Erdem Durum; Anıl Bayram; M.timuçin Aydın; Birol Ağca (Boğaziçi Tıp Dergisi, 2022)
INTRODUCTION: Peptic ulcer disease (PUD); it is caused by the disturbance of the balance between gastric acid-pepsin secretion and the mucous barrier. Approximately 4 million people around the world are affected by PUD every year. The incidence of PUD varies between 1.5 and 3% and complications are seen in approximately 10–20% of these patients. In this study, the efficiency of laparoscopic repair and conventional repair methods in Peptic ulcer perforation (PUP) treatment was compared. METHODS: A total of 169 patients who were operated for PUP between January 2011 and December 2019 were included in the study. Omental patch application with primary repair or only omental patch application techniques were applied to the perforation area for PUP repair. Patients in the study; age, gender, the American Society of Anesthesiologists (ASA) scores, operation times, peroperative and post-operative complications, hospitalization times, perforation locations, and reasons for readmission were evaluated and the information was retrospectively scanned and recorded in a previously prepared database. RESULTS: Post-operative complications were observed in 19.3% of the patients who underwent conventional repair, in 10.5% of the patients who underwent laparoscopic repair, and in 12.5% of the patients who converted to conventional repair from laparoscopic repair, and there was no statistically significant difference between them (p>0.05). Mortality developed in 11.3% of cases with conventional repair, in 10.8% of cases with laparoscopic repair, and in 12.5% of cases that converted to conventional repair from laparoscopic repair, and there is no statistically significant difference between them (p>0.05). DISCUSSION AND CONCLUSION: In this study, although there was no statistically significant difference in efficacy and safety between laparoscopic repair and conventional repair in PUP, we found that laparoscopic repair was advantageous over conventional repair in many aspects. We think that the surgical method to be chosen should be decided in line with the surgeon's experience.